2022
DOI: 10.1186/s12889-022-13943-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence mental health of university and college students in the UK: a systematic review

Abstract: Background Worsening mental health of students in higher education is a public policy concern and the impact of measures to reduce transmission of COVID-19 has heightened awareness of this issue. Preventing poor mental health and supporting positive mental wellbeing needs to be based on an evidence informed understanding what factors influence the mental health of students. Objectives To identify factors associated with mental health of students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 77 publications
0
48
0
Order By: Relevance
“…Finally, the research supports early intervention. Many studies have advocated that tailored (i.e., targeted toward specific populations) support services be in place for students when they arrive on campus (Gewalt et al, 2022) and others recommend that this intervention take place before they arrive on campus, with a focus on preparing students and their families for the transition to college (Campbell et al, 2022). This is an initiative with a great deal of potential that must be explored further.…”
Section: Recommendations For Academica Practice and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the research supports early intervention. Many studies have advocated that tailored (i.e., targeted toward specific populations) support services be in place for students when they arrive on campus (Gewalt et al, 2022) and others recommend that this intervention take place before they arrive on campus, with a focus on preparing students and their families for the transition to college (Campbell et al, 2022). This is an initiative with a great deal of potential that must be explored further.…”
Section: Recommendations For Academica Practice and Policymentioning
confidence: 99%
“…Although most colleges and universities re-opened in the fall of 2020, the pandemic has continued to negatively affect college students worldwide (Huckins et al, 2020). A recent systematic review found that the mental health of college students between the ages of 18 and 25 was disparately impacted by the pandemic across the UK (Campbell et al, 2022). A nationwide survey conducted in China found that mental health problems, including anxiety and depression, were widespread among Chinese college students during the pandemic (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of university students are also experiencing increasing poor mental health (Campbell et al, 2022 ). Boyd investigated the feasibility of using nature-based interventions with undergraduate students.…”
Section: Feasibility Of Prescribing Nature-based Social Prescriptionsmentioning
confidence: 99%
“…Around one-third of people worldwide develop a mental disorder at some point in their life ( Steel et al, 2014 ), and the onset of many mental disorders occurs in childhood or adolescence ( Carvalho et al, 2022 ). Mental disorders seriously affect adolescents’ mental health, wellbeing, academic performance and social relations ( Campbell et al, 2022 ) but very few seek professional help ( Seo et al, 2022 ) while others postpone obtaining support ( Jorm, 2012 ). Yet, delaying treatment makes treatment more difficult ( de Diego-Adeliño et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%